Study on Domestic Violence against women in Nepalese village of Terai Region - Giri, Shree Shyam; Singh, Jitendra Kumar; Giri, Radheshyam; Jha, Lalan Kumar; Yadav, Sushil K (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: The South East Asian Region has one of the highest incidences of gender based violence in the world which deprives women from the use of their right and liberty. This study was under taken to explore the causes and consequences of domestic violence against women in Meghanath Gorhanna VDC in Mahottari district of Nepal. Material and Methods: : An explorative quantitative and qualitative research design based study was conducted from September to December 2014 in married female of ward, No. 1, 2 and 4 of Meghanath Gorhanna VDC which is located in Mahottari district of Nepal suffering from domestic violence. Sample size consisted of 20 in each ward and sum of total was 60. In-depth interviews, focused group discussion and observation were tools used for data collection. Results: The result of this study reveals that 40% of victims were between age group 20 to 29 years. Domestic violence was higher among illiterate 20(33%). 12(20%) of the women were victimized due to alcoholism of their husband followed by male honor and patriarchal social values. Similarly, majority of the respondents 47(78.3%) suffered from psychological abuse followed by physical assault. 20(33.3%) women were suffered from physical violence. 10% women were suffered from sexual abuse and harassment. The findings also suggest 23(35%) had mental health problem and 14(23 %) women were suffered from reproductive health problem. Conclusion: The study highlights that various factors such as excessive intake of alcohol, patriarchal system of the society, polygamy, sexual dissatisfaction and dowry contributes for the domestic violence in women. The adverse effects of the violence on women are physical health problem, mental health problem, reproductive health problem, chronic conditions and negative health behavior. Janaki Medical College Journal of Medical Sciences (2016) Vol. 4(1): 46-52